DINAMIKA IDENTITAS BUDAYA MELAYU DALAM TINJAUAN ARKEO-ANTROPOLOGIS - Arditya Prayogi (Fakultas Adab dan Humaniora UIN Raden Fatah, 2016)
Discourse on Malay is still evolving. Among the discourse is about the identity of the nation-state known as the Malay race. Various scientific approaches have been used in the search for common ground in this discourse, one of which is arkeo-anthropological approach. Arkeo-anthropological approach in view of the Malay cultural identity remains focused on human material Malays, particularly referring to the reality of the human origins of Malay as the owner of Malay culture. In this case then, arkeo-anthropological approach directs the discourse about Malay in search of human traces and remains of the ancient Malay culture. This paper uses arkeo-anthropological approach of looking at the human who the owner of the Malay culture.